Визначення критерія кавітації лабіринтно-гвинтового насоса - Лебедєв, Антон Юрійович (НТУ "ХПІ", 2013)
The method of calculation and value of criterion of cavitations of labyrinth-spiral pump is resulted in the article. The analysis of influence of structural and working parameters of pump and properties of working liquid is conducted on this criterion. Finding allows during the design of such pumps to estimate probability of origin of cavitations on his entrance.
Keywords: рідина робоча; газовміст; тиск пароутворення; насособудування